Predictive and Prognostic Roles of Gut Microbial Variation in Liver Transplant - Wong, Hon Jen; Lim, Wen Hui; Ng, Cheng Han; Tan, Darren Jun Hao; Bonney, Glenn K.; Kow, Alfred W. C.; Huang, Daniel Q.; Siddiqui, Mohammad Shadab; Noureddin, Mazen; Syn, Nicholas; Muthiah, Mark D. (Frontiers in Medicine, 2022)
Patients expecting to get well after liver transplant (LTX) are often met with postoperative complications. A dysbiotic gut microbiome is associated with the development of complications, including post-LTX allograft rejection, metabolic disease and cancer. A facet of this would be its ability to exert considerable influence over local immunity. It regulates the alloimmune response towards the liver allograft and is implicated in the pathogenesis of hepatocellular carcinoma and extrahepatic de novo malignancies. Alongside increased bacterial translocation from dysbiosis, dysregulated immunity causes pathogenic changes in the concentrations of microbial products like Lipopolysaccharides, Short-chain fatty acids and Trimethylamine-N-Oxide, with links to cardiovascular disease development. Dysbiosis disrupts bile acid metabolism, which implies its role in post-LTX metabolic diseases like post-transplant diabetes mellitus. Of note, certain species of microbiota are associated with these undesired outcomes. As follows, clinical modulation of a dysbiotic modulation towards a beneficial composition may aid in recovery or decrease complication risk in LTX patients. Additionally, there are roles of the microbiome as predictive and prognostic indicators for clinicians in improving patient care. Hence, the gut microbiome is a potentially relevant and impactful therapeutic strategy for post-LTX patient care, where further studies should be carried out to fully utilize its potential.